PERSEPSI MAHASISWA UNIVERSITAS AL ASYARIAH MANDAR TERHADAP PESAN BAHAYA MEROKOK PADA KEMASAN ROKOK - Muh. Misraj Majid; Muhammad Massyat; Masyhadiah Masyhadiah (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
This study aims to determine how the perception of Al-Asyariah Mandar University students towards the message of the dangers of smoking on cigarette packaging. The research used is descriptive qualitative to describe studying and understanding the attitudes, views, and behavior of individuals or groups. The results obtained are several active and passive smoker informants support the provision of warning images on cigarette packaging. But there are also those who think it's normal because they have never seen anything in person or confessions from people who have felt the bad effects like what happened in the picture on the cigarette package. Some informants saw that the warning pictures of the dangers of smoking gave them past experiences that could be a factor in forming their perceptions in the future.